2014
DOI: 10.1007/s10863-014-9561-0
|View full text |Cite
|
Sign up to set email alerts
|

Modelling mechanism of calcium oscillations in pancreatic acinar cells

Abstract: We present a simple model for calcium oscillations in the pancreatic acinar cells. This model is based on the calcium release from two receptors, inositol trisphosphate receptors (IPR) and ryanodine receptors (RyR) through the process of calcium induced calcium release (CICR). In pancreatic acinar cells, when the Ca²⁺ concentration increases, the mitochondria uptake it very fast to restrict Ca(2+) response in the cell. Afterwards, a much slower release of Ca²⁺ from the mitochondria serves as a calcium supply i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(10 citation statements)
references
References 113 publications
0
10
0
Order By: Relevance
“…1,2 Attempts are reported in the literature for the study of calcium regulation in neuron cell, astrocyte cell, fibroblast cell, oocyte cell, acinar, etc. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] But very few attempts are reported in the literature for the study of calcium dynamics in myocytes. 1,2,20,21 Most of the studies reported on calcium diffusion in myocytes are experimental.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Attempts are reported in the literature for the study of calcium regulation in neuron cell, astrocyte cell, fibroblast cell, oocyte cell, acinar, etc. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] But very few attempts are reported in the literature for the study of calcium dynamics in myocytes. 1,2,20,21 Most of the studies reported on calcium diffusion in myocytes are experimental.…”
Section: Introductionmentioning
confidence: 99%
“…Although RYRs might be involved in Ca 2+ oscillations (Kannan et al, 1997;McHale et al, 2006;Nakayama et al, 2005;Plummer et al, 2011), studies suggest that Ca 2+ oscillations are mainly generated by the activation of IP3R release channels in many cell types (Abou-Saleh et al, 2013;Berridge, 2007;Hruby et al, 2008;Manhas and Pardasani, 2014;Martin-Cano et al, 2009;Tamarina et al, 2005;Tamashiroand Yoshino, 2014). Our results suggest that the Ca 2+ oscillations induced by the stretching of mouse bladder smooth myocytes was mainly mediated the activation of IP3Rs by NO production, although it was impossible to completely exclude the involvement of RYRs.…”
Section: Discussionmentioning
confidence: 99%
“…Pathak et al [18] have developed a two dimensional mathematical model to understand Ca 2+ signaling process in cardiac myocyte but they have not considered the impact of IP 3 dynamics in their model. There are other studies of different cells in literature like hepatocytes [19], neurons [20,21], astrocytes [22,23], fibroblasts [24,25], pancreatic acinar [26,27] and oocytes [28]. But in the existing literature, many mathematical work on Ca 2+ signaling in cardiac myocyte have not paid attention on the role of IP 3 signaling in their mathematical model [29] while those works which state about the impact of IP 3 signaling on Ca 2+ signaling are experimental [30,31,32].…”
Section: Introductionmentioning
confidence: 99%